Adapting the eighteenth century : a handbook of pedagogies and practices - Harrow, Sharon; Saxton, Kirsten T., 1965- (University of Rochester Press, 2020)
"A collection of pedagogical essays that presents proven strategies for the teaching of adaptation and eighteenth-century texts"--